Analisis Sistem Mata Pencaharian On-fishing dan On-farm Rumah Tangga Nelayan Sama Bajo Torokeku - Nur Isiyana Wianti; Tjandra Buana; Suriana Suriana; Sukmawati Abdullah; Muslim Tadjuddah (Universitas Halu Oleo, 2021)
This study is set out to explore a livelihood system of on-fishing and on-farm activities in Sama Bajo Small-Scale Fisher (SSF) community in the middle of their socio-ecological issues and at the beginning of COVID-19 disruptions impact. Fieldwork in Torokeku Village, South Konawe Regency, South-east Sulawesi Province was conducted in September 2020 by using qualitative research method to explore rigorously about the research objective. Moreover, several in-depth interviews were conducted with those who were selected purposively. They are the active fishers and represented a group of people based on the village social stratification and various livelihoods. We also obtained the data through participant observations. Here, we found that on-fishing and on-farm of Sama Bajo Torokeku livelihood activities are a higher degree of risk due to a horizontal social conflict, seasonality, ecological degradation, and COVID-19 disruptions particularly to Sama Bajo Torokeku Blue Swimming Crab fishers and Seaweed farmers. However, in this research, there is a lack of clarity due to limited studies on gender dimension on the on-fishing and on-farm livelihood activities, thereby future research has to take into account women’s contributions in Sama Bajo livelihood system analysis as a base of fisheries management policy.